3D Raman mapping of uniaxially loaded 6H‐SiC crystals. (4th February 2013) - del, E.; Izquierdo, J. G.; González, J.; Taravillo, M.; Baonza, V. G.
<x xml:space="preserve">Abstract</x> Raman spectroscopy is used to investigate the three‐dimensional stress distribution in 6H‐silicon carbide (SiC) specimens subjected to stresses up to 3.7 GPa along the c‐axis. Specifically, the relative Raman shift of the longitudinal optic phonon of 6H‐SiC is used to evaluate the local stress across the bulk crystal. For this purpose, an anvil device with opposed 6H‐SiC and sapphire specimens was used. After subjecting the anvils to uniaxial load, several series of two‐dimensional Raman maps were registered at different depths in the 6H‐SiC anvil. The analysis of the Raman spectra reveals an exponential decay of the stress as a function of the depth. A novel phenomenological Grüneisen‐like model is introduced here to account for such observation. On the contrary, the in‐plane stress analysis shows a radial Gaussian‐like distribution regardless the depth, a distinct behavior that is attributed to the appearance of shear stress components. The suitability of both models and their applicability to other materials are discussed, along with some future directions. Copyright © 2013 John Wiley & Sons, Ltd.